[Date Index]
[Thread Index]
[Author Index]
Why can't FullSimplify give more uniform output?
*To*: mathgroup at smc.vnet.net
*Subject*: [mg119734] Why can't FullSimplify give more uniform output?
*From*: Jacare Omoplata <walkeystalkey at gmail.com>
*Date*: Sun, 19 Jun 2011 19:28:53 -0400 (EDT)
Hello,
I ask this question just out of curiosity.
Below is my input and output. The expressions "s" and "dT" are equal,
as can be seen by Out[17]. But the output from FullSimplify is
different for those two as can be seen by Out[12] and Out[15]. Why
can't they be simplified to expressions that look alike?
Thanks.
(PS. Also please tell me if my code is inefficient. I'm still learning
Mathematica)
In[1]:= Element[{x1, x2, t1, t2, u, c}, Reals]
Out[1]= (x1 | x2 | t1 | t2 | u | c) \[Element] Reals
In[7]:= $Assumptions = {u > 0, c > u}
Out[7]= {u > 0, c > u}
In[9]:= T1 = (t1 - ((u x1)/c^2))/Sqrt[1 - (u^2/c^2)]
Out[9]= (t1 - (u x1)/c^2)/Sqrt[1 - u^2/c^2]
In[10]:= T2 = (t2 - ((u x2)/c^2))/Sqrt[1 - (u^2/c^2)]
Out[10]= (t2 - (u x2)/c^2)/Sqrt[1 - u^2/c^2]
In[11]:= dT = T2 - T1
Out[11]= -((t1 - (u x1)/c^2)/Sqrt[1 - u^2/c^2]) + (
t2 - (u x2)/c^2)/Sqrt[1 - u^2/c^2]
In[12]:= FullSimplify[dT]
Out[12]= (c^2 (-t1 + t2) + u (x1 - x2))/(c Sqrt[(c - u) (c + u)])
In[14]:= s = (t2 - t1 - ((u/c^2)*(x2 - x1)))/Sqrt[1 - ((u^2)/(c^2))]
Out[14]= (-t1 + t2 - (u (-x1 + x2))/c^2)/Sqrt[1 - u^2/c^2]
In[15]:= FullSimplify[s]
Out[15]= (c (-t1 + t2 + (u (x1 - x2))/c^2))/Sqrt[(c - u) (c + u)]
In[16]:= s - dT
Out[16]= (t1 - (u x1)/c^2)/Sqrt[1 - u^2/c^2] - (t2 - (u x2)/c^2)/Sqrt[
1 - u^2/c^2] + (-t1 + t2 - (u (-x1 + x2))/c^2)/Sqrt[1 - u^2/c^2]
In[17]:= FullSimplify[s - dT]
Out[17]= 0
Prev by Date:
**Why doesn't TrueQ return True here?**
Next by Date:
**How to find one expression in terms of another expression?**
Previous by thread:
**Re: Why doesn't TrueQ return True here?**
Next by thread:
**Re: Why can't FullSimplify give more uniform output?**
| |